Bioequivalence study of low dose drospirenone/ethinyl estradiol 3 mg/0.03 mg film tablets under fasting conditions in Turkish healthy female subjects - Ahmet Inal; Zafer Sezer; Berna Uluözlü; Melih Oflas; Martin Reinsch; Wolfgang Martin; Mümtaz M. Mazicioglu; Selma Alime Koru (Wiley, 2024)
Abstract This bioequivalence research aims to evaluate the relative bioavailability and pharmacokinetic characteristics of ethinyl estradiol and drospirenone in the test preparation in comparison to the reference preparation during fasting conditions. A liquid chromatography method with tandem mass spectrometry was used to determine the concentrations of drospirenone and ethinyl estradiol in plasma. The pharmacokinetic parameters that were analyzed were the maximum plasma concentration (Cmax), time to achieve Cmax (tmax), elimination half life, and area under the concentration time curve of plasma (AUC0‐t, AUC0‐∞ for ethinyl estradiol, and AUC0‐72h for drospirenone). Both the AUC and Cmax parameters were determined to be between 80.00% and 125.00% (90% confidence intervals), which is the acceptable range. Based on the study findings, it was concluded that the test formulation, which includes 3 mg of drospirenone and 0.03 mg of ethinyl estradiol, demonstrated bioequivalence when compared to the reference formulation.